2018
DOI: 10.1159/000495673
|View full text |Cite
|
Sign up to set email alerts
|

MORC2 Enhances Tumor Growth by Promoting Angiogenesis and Tumor-Associated Macrophage Recruitment via Wnt/β-Catenin in Lung Cancer

Abstract: Background/Aims: In this study, we aimed to investigate how MORC family CW-type zinc finger 2 (MORC2) affects tumor progression of lung cancer. Methods: The MORC2 level was analyzed by real-time RT-PCR and immunohistochemistry (IHC) in normal control tissues and lung cancers. LL/2 cells overexpressing MORC2 were used to study how MORC2 expression influences lung cancer progression. The effects of MORC2 on cell viability, migration and invasion were assessed by MTT assay, Western blotting, and transwell assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Many studies have investigated the functional mechanisms of lncRNA BLACAT1 on tumorigenesis and progression in various cancers. Wnt/ β -catenin signal pathway has been confirmed to be involved in the regulation of cell proliferation, migration, and invasion in certain cancers [25, 26]. Wang et al reported that knockdown of lncRNA BLACAT1 might inhibit the proliferation, migration, and invasion of cervical cancer cells by suppressing the activation of Wnt/ β -catenin signal pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the functional mechanisms of lncRNA BLACAT1 on tumorigenesis and progression in various cancers. Wnt/ β -catenin signal pathway has been confirmed to be involved in the regulation of cell proliferation, migration, and invasion in certain cancers [25, 26]. Wang et al reported that knockdown of lncRNA BLACAT1 might inhibit the proliferation, migration, and invasion of cervical cancer cells by suppressing the activation of Wnt/ β -catenin signal pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it possibly plays an important role in drug resistance and disease recurrence (14). In addition, activating Wnt/-catenin signaling in tumor cells modulates the recruitment of immune cells, particularly macrophages and T cells in TME (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…SNHG20 acted/function as an oncogene to interact with EZH2 to inhibit the expression of E-cadherin and p21 in the GC and NSCLC cells [12,28]. Wnt/β-catenin signal pathway has been revealed to be involved in the regulation of cell proliferation, migration, and invasion in certain cancers [29,30]. It was reported that lncRNA SNHG20 could promote the proliferation, migration, and invasion of bladder cancer and ovarian cancer by activating the Wnt/β-catenin signal pathway [27,31].…”
Section: Discussionmentioning
confidence: 99%